Local Wisdom in Arabic Calligraphy on The Yogyakarta’s Palace Building - Saidah, Nur (Proceeding International Conference on Religion, Science and Education, 2022)
This paper is the result of research on Arabic calligraphy in the Palace of Yogyakarta building in the range of the XVIII - XX century AD, which is a unique historical phenomenon of the spread of Islamic religion and culture, because the form of calligraphy is distilled (stylize) and becomes unusual in the community in the Palace of Yogyakarta which strongly holds Javanese culture. The question are, why Arabic calligraphy was applied in the Palace of Yogyakarta building in the XVIII - XX century AD, how the various graphic visual forms, meanings, and historical relationships with the social dynamics and the struggles of religious ideas that underlying them. Through historical method, the results showed: First, the factor of the emergence of Arabic calligraphy, internally, because of the encouragement of Sultan HB I to rebuild the Islamic Mataram kingdom. Second, the variety of Arabic calligraphy includes decorations on the saka / pillars of the main building of the Palace and buildings devoted to the Sultan. The type of writing used is figural / stylistic and symbolic, a distinctive blending between local genius and Islamic kha?. From the aspect of meaning there is a peculiarity of meaning combined with myth which is a shift in meaning from Javanese, Hindu and Buddhist cultural concepts to meaning in Islamic concepts and functions as a spiritual expression that contains political elements. The text contains: a) verse of Al-Qur'an, b) lafadz jalalah, c) name of the Prophet Muhammad SAW. Third, from the selection of verbal signs / calligraphy contents, and their style, it shows that there is a sporadic and symbolistic tendency to establish the Yogyakarta Palace as a political institution that continues the Islamic mission of the Islamic Mataram Kingdom with an Islamic style in a Javanese perspective.